The Effect of Administering A Combination of Bay Leaf Boiled Water and Honey on Decreasing Mean Arterial Pressure (MAP) in Prelaines with Hypertension - Rapika, Nor; Tasalim, Rian; Mahdiyah, Dede; Redjeki, Dwi Sogi Sri (GLOBAL HEALTH SCIENCE GROUP, 2024)
Hypertension is often referred to as a